Humid, All Too Humid: Overheated Observations - Pettman, Dominic (Book collections on Project MUSE., 2020)
In Humid, All Too Humid, social commentator Dominic Pettman curates the overheated thoughts of his own feverish mind, in response to a world struggling with unprecedented levels of cultural climate change. The book takes the form of aphorism, witticism, maxim, axiom, dictum, quip, jape, adage, proverb, pun, precept, reflection, suggestion, observation, paraphrase, bon mot, vagary, specificky, put-on, put-off, mummery, miscellany, aside, in-front, behind, knock-knock joke, one-liner, tweet, re-tweet, truism, and not-so-truism. Known for his scholarly work on love, sex, and the (post)human condition, Pettman now assembles this collection of humoristic micro-meditations on everything from the meaning of life to the "yoghurt of human unkindness." Humid, All Too Humid reads as if Oscar Wilde had first written Minima Moralia, after binge-watching too many episodes of The Simpsons.